Spatiotemporal coupling of the hepatitis C virus replication cycle by creating a lipid droplet- proximal membranous replication compartment - Lee, Ji Young; Cortese, Mirko; Haselmann, Uta; Tabata, Keisuke; Romero-Brey, Inés; Funaya, Charlotta; Schieber, Nicole L.; Qiang, Yu; Bartenschlager, Marie; Kallis, Stephanie; Ritter, Christian; Rohr, Karl; et al. (Cell reports, 2019)
The hepatitis C virus (HCV) is a major cause of chronic liver disease, affecting around 71 million people worldwide. Viral RNA replication occurs in a membranous compartment composed of double-membrane vesicles (DMVs), whereas virus particles are thought to form by budding into the endoplasmic reticulum (ER). It is unknown how these steps are orchestrated in space and time. Here, we established an imaging system to visualize HCV structural and replicase proteins in live cells and with high resolution. We determined the conditions for the recruitment of viral proteins to putative assembly sites and studied the dynamics of this event and the underlying ultrastructure. Most notable was the selective recruitment of ER membranes around lipid droplets where structural proteins and the viral replicase colocalize. Moreover, ER membranes wrapping lipid droplets were decorated with double membrane vesicles, providing a topological map of how HCV might coordinate the steps of viral replication and virion assembly.